1988
DOI: 10.1139/f88-121
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Significance of the Topographical Distribution of Blubber in Ringed Seals (Phoca hispida)

Abstract: The distribution of blubber in ringed seals (Phoca hispida) and relationships between surface area, body mass, and linear dimensions are described. The blubber was distributed in such a way that the ratio of blubber thickness to body radius is nearly constant over the body, maximizing the available blubber for insulation. The hind part of the body has a higher thickness to radius ratio and is thus "overinsulated." During periods of mass loss, fat is lost fastest from this overinsulated region, thus reducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 4 publications
5
84
2
Order By: Relevance
“…In a study of the topographical distribution of blubber in ringed seals, Ryg et al (1988) found that the ratio of blubber thickness to body radius was nearly constant over the body, thereby maximising the blubber available for insulation. The hind part of the body had a higher thickness to radius ratio and was therefore considered to ..jLength/ Mass· blubber thickness be "over-insulated".…”
Section: Thermoregulationmentioning
confidence: 99%
“…In a study of the topographical distribution of blubber in ringed seals, Ryg et al (1988) found that the ratio of blubber thickness to body radius was nearly constant over the body, thereby maximising the blubber available for insulation. The hind part of the body had a higher thickness to radius ratio and was therefore considered to ..jLength/ Mass· blubber thickness be "over-insulated".…”
Section: Thermoregulationmentioning
confidence: 99%
“…A cylindrical model, illustrated in Fig. 1, has also been supposed by other authors (Ryg et al, 1988;Lavigne et al, 1990;Watts et al, 1993).…”
Section: The Modelmentioning
confidence: 69%
“…Different models have been used to estimate heat exchange in marine mammals (Innes, 1986;Kshatriya & Blake, 1988;Ryg et al, 1988;Hokkanen, 1990;Watts et al, 1993), but the results vary widely, which is probably explained by the practical difficulties entailed in measuring body surface temperature of these animals. This paper presents an iterative method of predicting the skin temperature of cetaceans using deep body temperature, swimming speed, and the temperature and thermodynamic properties of the water.…”
Section: Introductionmentioning
confidence: 99%
“…Blubber thickness was measured to the nearest mm at a point dorsally, located 60% of the length along a straight line from the tip of the nose. The blubber thickness at this point has been shown to be highly sensitive to changes in body condition in ringed seals (Phoca hispida; Ryg et al 1988) and harp seals (Phoca groenlandica; Beck et al 1993). Canine teeth from the upper or lower jaws were taken for age determination.…”
Section: Methodsmentioning
confidence: 99%
“…Seasonal variation in the condition of adult bearded seals was analyzed based on blubber thickness measurements (Ryg et al 1988) and by using a condition index (CI) (American Society of Mammalogists 1967):…”
Section: Methodsmentioning
confidence: 99%